2018
DOI: 10.1371/journal.pone.0191123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different radio-opacifying agents on physicochemical and biological properties of a novel root-end filling material

Abstract: Background/PurposeRadio-opacity is an essential attribute of ideal root-end filling materials because it is important for clinicians to observe root canal filling and to facilitate the follow-up instructions. The novel root-end filling material (NRFM) has good cytocompatibility and physicochemical properties but low intrinsic radio-opacity value. To improve its radio-opacity value, three novel radio-opaque root-end filling materials (NRRFMs) were developed by adding barium sulphate (NRFM-Ba), bismuth trioxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 45 publications
2
10
1
2
Order By: Relevance
“…This finding is in accordance to one recent study performed on a novel root-end filling material. [23] but in contrast to another study. [24] which could be attributed to different materials used and methodological procedures for measuring the pH values.…”
Section: Discussioncontrasting
confidence: 89%
“…This finding is in accordance to one recent study performed on a novel root-end filling material. [23] but in contrast to another study. [24] which could be attributed to different materials used and methodological procedures for measuring the pH values.…”
Section: Discussioncontrasting
confidence: 89%
“…[36][37][38] In addition, studies have shown that ZrO 2 is more biocompatible than Bi 2 O 3 and BaSO 4 . 39 Therefore, ZrO 2 was chosen as a radiopacity agent in the present study and the sealer 20%MgO/TMP was chosen in tests which need the addition of ZrO 2 due to its high antibacterial rate and physicochemical properties and then the radiopacity was tested, and physicochemical properties, antibacterial properties and cytotoxicity of the sealer with ZrO 2 incorporation were evaluated. It was reported that materials with the addition of 20% ZrO 2 could present higher radiopacity values than those of bone or dentin.…”
Section: Discussionmentioning
confidence: 99%
“…Por ello, es relevante considerar la biocompatibilidad de los agentes radiopacos que se agregan y que podrían ser liberados con el tiempo. Con respecto óxidos de agentes radiopacos, como el de bario, se ha cuestionado su biocompatibilidad, a diferencia de otros agentes radiopacos, como el zirconio que es considerado químicamente inerte y biocompatible (22,23) .…”
Section: Discussionunclassified